EMG analysis of shoulder muscles during preventive and therapeutic exercise in the overhead athlete - Grigereit, A.; Ziesing, A.; Vogt, L.; Banzer, W. (Medicine and Science in Tennis, 2004)
Strengthening of the rotator cuff muscles in functional positions is important for the prevention and rehabilitation of shoulder injuries in overhead athletes such as tennis, badminton and volleyball players. The purpose of this study was to evaluate the influence of exercise with a new shoulder bar (SBT 1000) on the myoelectric activity of the deltoid muscle.